Prioritization of Inside Urban Space Indicators Using Delphi Method (Case study: Gorgan City) - Fateme Hajizade; Seyed Hamed Mirkarimi; Abdorassuol Salman Mahini; Marjan Mohammadzade (تحقیقات کاربردی علوم جغرافیایی)
Cities are open systems that constantly change and bring about changes in inside and outside neighboring areas. With the rapid growth of urban population in the world, cities sprawl and occupy surrounding lands. In this situation, attention to the developments inside urban space could be a key principle in urban planning. The aim of this study was determining and prioritizing economic, social and ecological factors which influence inside urban space indicators in City of Gorgan using Delphi method and literature review. Following the increase in population, developments inside urban space in the future is inevitable. Understanding and recognition of this process is essential to effective management in the field of conservation of the urban environment. Four expertize requirements should be taken into account: knowledge and experience of the field of study; ability and willingness to participate; adequate time to participate; and effective communication skills. Experts’ panel included fifteen specialists from municipality, city council, academics, cultural and medical service providers, police, urban planners and citizens, whose points of view were collected using questionnaires. Data collection for questionnaire was repeated 4 times to reach a consensus. Overall, twenty - four factors were identified for the economic, social and ecological factors, and then the degree and percentage of importance for each one was determined. Results showed that the most important indicator is feeling of security followed by the noise pollution and environmental pollution. Results could be helpful to urban planners and related organizations to improve inside urban space for welfare and life quality of citizens. Prioritization of these indicators provides an appropriate action agenda for the managers.